Pengaruh Pengembangan Kawasan Ekonomi Khusus Pariwisata terhadap Pembangunan Wilayah - Amanda Ayulindia Syarmalina; Hera Susanti (Jurnal Syntax Admiration, 2024)
This study analyzes the influence of the development of Tourism Special Economic Zones (SEZs) on regional development, focusing on economic growth, poverty, and unemployment in the area around the SEZ. Using spatial econometrics methods, this study includes four SEZs: Tanjung Lesung, Mandalika, Morotai, and Tanjung Kelayang. The results show that Tourism SEZs have a positive impact on economic growth in certain regions, especially Tanjung Lesung, although their impact on the surrounding areas is still limited. Poverty and unemployment showed varied outcomes; some SEZs have decreased, but the influence has not been significantly evenly distributed. Domestic tourists play an important role in supporting economic growth, with variables of tourist attraction and accommodation capacity having a positive impact. However, the effectiveness of Tourism SEZs is still constrained by limited infrastructure and local community empowerment. The study emphasizes the importance of facility development and community involvement to optimize the benefits of SEZs as a new economic growth center.